1960
DOI: 10.1071/zo9600217
|View full text |Cite
|
Sign up to set email alerts
|

Life history of Acanthoparyphium spinulosum Johnston, 1917 (Trematoda: Echinostomatidae).

Abstract: A list is given of the trematode cercariae which are commonly found in the estuarine gastropod, Pyrazus australis Quoy & Gaimard. These include: cercariae of a schistosome, Austrobilharzia terrigalensis Johnston, 1917, and of a heterophyid, Stictodora sp.; a monostomate xiphidiocercaria, probably belonging to the Microphallidae; two megalurous cercariae, probably belonging to the Philophthalmidae; and one echinostome cercaria. The life history of the latter, Acanthoparyphium spinulosum Johnston, 1917, is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Brackish water gastropods, bivalves, or oysters play the role of a first or second intermediate host, or both [1][2][3][4][5][6][7][8].In the Republic of Korea, Chai et al [7] reported recently that Acanthoparyphium tyosenense Yamaguti, 1939 causes human infections. The complete life history of A. tyosenense has been previously elucidated; several species of brackish water mollusks have been demonstrated to harbor the metacercariae of A. tyosenense [7,9,10].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Brackish water gastropods, bivalves, or oysters play the role of a first or second intermediate host, or both [1][2][3][4][5][6][7][8].In the Republic of Korea, Chai et al [7] reported recently that Acanthoparyphium tyosenense Yamaguti, 1939 causes human infections. The complete life history of A. tyosenense has been previously elucidated; several species of brackish water mollusks have been demonstrated to harbor the metacercariae of A. tyosenense [7,9,10].…”
mentioning
confidence: 99%
“…The natural definitive hosts of Acanthoparyphium are always aquatic birds, and the majority of them are migratory; some of them, like plovers, godwits, knots, and dotterels fly from Siberia to southern Australia [1][2][3][4][5]. Human infections were reported only in 1 species, A. tyosenense [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…of the people. Bearup, Lawrence and Heydon (1949) found that 1.3 per cent. of 2,365 recruits to the armed forces who had never been out of Australia were passing Entamoeba histolytica cysts.…”
mentioning
confidence: 96%